ANALISIS PENGARUH VARIASI WAKTU PERLAKUAN ALKALI TERHADAP KEKUATAN IMPACT KOMPOSIT POLYESTER YANG DIPERKUAT SERAT BAMBU - Kadek Rihendra Dantes; I Nyoman Pasek Nugraha; Edi Elisa; I Putu Heri Yudistira (Jurnal Rekayasa Mesin, 2023)
This study aimed to determine the effect of alkali treatment on the impact strength and fracture pattern of bamboo fiber reinforced polyester composites. This composite consisted of polyester resin as a matrix and bamboo fiber as a filler or reinforcement. The alkaline treatment time used was 5% NaOH from 1 hour to 4 hours and to determine the microscopic image of the fracture pattern of the impact test specimen. This study used an experimental method with the dependent variable being the impact strength and microscopic images of the fracture pattern, and the independent variable was the alkali treatment time 1 hour, 2 hours, 3 hours and 4 hours. Specimens were printed using the hand lay-up method. The impact strength was known by performing consecutive tests based on ASTM D 6110-04. Based on the results of the impact test, it showed that the impact strength increased until the alkaline treatment 2 hours ago and decreased at 3 hours, and 4 hours. The highest impact strength was shown in the alkaline treatment of bamboo fiber rope 2 hours with an impact strength value of 1373.89 J/M2. The examination of the microscopic image of the fracture pattern obtained the best fracture in 2 hours alkali treatment with a brittle fracture mechanism.